Identification of a Molecular Target of a Novel Fungal Metabolite, Pyrrolizilactone, by Phenotypic Profiling Systems. Issue 18 (25th October 2013) - Futamura, Yushi; Kawatani, Makoto; Muroi, Makoto; Aono, Harumi; Nogawa, Toshihiko; Osada, Hiroyuki
Abstract In the course of screening our microbial metabolite fraction library, we identified a novel pyrrolizidinone compound, pyrrolizilactone. In this study, we report the identification and characterization of a molecular target for pyrrolizilactone by using two phenotypic profiling systems. Cell morphology‐based profiling analysis using an imaging cytometer (MorphoBase) classified pyrrolizilactone as a proteasome inhibitor. Consistently, proteome‐based profiling analysis using 2D difference gel electrophoresis (DIGE; ChemProteoBase) also demonstrated that pyrrolizilactone is associated with proteasome inhibition. On the basis of these predictions, we determined that pyrrolizilactone is a novel type of proteasome inhibitor inhibiting the trypsin‐like activity of the proteasome.